Lectotypification of three names in the genus Tripogon (Poaceae) - Kottekkattu, Thoiba; Pradeep, A.k. (Phytotaxa, 2018)
Three names in Tripogon Roem. & Schult.: T. jacquemontii Stapf, T. lisboae Stapf and T. wightii Hook.f. are lectotypified here. Among seven specimens considered as original materials available at K, Jacquemont 320 (K000245018) perfectly agreeing with the protologue is selected as the lectotype of T. jacquemontii. Within the four various specimens cited in the protologue available at K, collection by Lisboa 03 (K barcode K0005013) with the drawings of floral parts with annotations by the author is selected as the lectotype of T. lisboae. Since only one specimen (Wight 1793 ?, K barcode K000245012) was cited in the protologue of T. wightii, it is designated as the lectotype of T. wightii.